ANALISIS KINERJA SAHAM BANK SYARIAH INDONESIA SATU TAHUN PASCA MERGER (STUDI KASUS BANK SYARIAH INDONESIA, TBK) - Hizrian Setiawan; Muchlis Muchlis (Journal of Accounting, Management and Islamic Economics, 2023)
This study reveals the performance of Bank Syariah Indonesia, compared to the performance of BRISyariah which is one of the banks that merged into BSI. Prior to the merger, there were three Sharia Banks owned to the state-owned Bank Association, namely Bank BRISyariah (BRIS) which had gone public, as well as Bank BNI Syariah (BNIS) and Bank Syariah Mandiri (BSM) which had not gone public. BSI's financial performance is better than the financial performance of BRIS, BNIS, and BSM as can be seen from the income statement and balance sheet, as well as from financial ratios such as ROA, ROE, EM, PM and AU. BSI's stock performance is also better than the stock performance of BRIS, as can be seen from PER and PBV. The improvement in financial performance and stock performance after the merger shows that the synergy and increased economies of scale resulting from the merger have had a positive impact on the bank's financial performance, which has also been appreciated by shareholders on the stock exchange. Meanwhile, the analysis of BSI's stock beta shows that the number after the merger is higher than the BRIS beta before the merger. However, the increase in beta cannot be concluded as an increase in systematic risk, because the beta of BNIS and BSM are not yet known.